Long-read sequencing for 29 immune cell subsets reveals disease-linked isoforms - Inamo, Jun; Suzuki, Akari; Ueda, Mahoko Takahashi; Yamaguchi, Kensuke; Nishida, Hiroshi; Suzuki, Katsuya; Kaneko, Yuko; Takeuchi, Tsutomu; Hatano, Hiroaki; Ishigaki, Kazuyoshi; Ishihama, Yasushi; Yamamoto, Kazuhiko; et al. (Nature communications, 2024)
Alternative splicing events are a major causal mechanism for complex traits, but they have been understudied due to the limitation of short-read sequencing. Here, we generate a full-length isoform annotation of human immune cells from an individual by long-read sequencing for 29 cell subsets. This contains a number of unannotated transcripts and isoforms such as a read-through transcript of TOMM40-APOE in the Alzheimer’s disease locus. We profile characteristics of isoforms and show that repetitive elements significantly explain the diversity of unannotated isoforms, providing insight into the human genome evolution. In addition, some of the isoforms are expressed in a cell-type specific manner, whose alternative 3’-UTRs usage contributes to their specificity. Further, we identify disease-associated isoforms by isoform switch analysis and by integration of several quantitative trait loci analyses with genome-wide association study data. Our findings will promote the elucidation of the mechanism of complex diseases via alternative splicing. This paper unveils the complexity of human immune cell splicing, highlighting cell-specific isoforms and establishing connections between alternative splicing and complex traits. These findings have implications for understanding diseases and the evolution of the genome.